Data Collection in Flood-Prone Housing Areas of Balangan and Tabalong Regencies - Hanny Maria Caesarina; Juniar I La Sinta (UrbanGreen Central Media, 2026)
Flooding is one of the most frequent natural disasters in South Kalimantan. To prevent future disaster-related crises, it is essential to gather data regarding the rehabilitation of homes for disaster victims. This community service identified housing units in disaster-prone areas by directly involving the community in verifying the collected data. The methodology was Participatory Rural Appraisal (PRA). Results indicate that in Balangan Regency, the initial count of housing units prior to community verification was 10,507; following verification, this number was adjusted to 3,965 units. The areas with the highest concentration of affected units were Awayan (29.3%), Juai (27.4%), and Halong (18.7%), while Paringin (1.4%) had the lowest. In Tabalong Regency, the initial count was 11,791 units, which was revised to 3,106 units after community verification. The areas with the highest concentration of affected units were Tanjung (39.77%), Muara Harus (22.86%), and Murung Pudak (11.62%), while Upau (1.61%) had the lowest.